SANITARY LOSSES IN WARS OF THE LAST 100 YEARS, CHANGES IN THEIR STRUCTURE, AND THE IMPACT OF MEDICAL ASSISTANCE AT THE TACTICAL STAGE - Nodir N. Kobilov (Central Asian Journal of Medicine, 2025)
The article presents data on losses in wars over the past 100 years. In the process of studying the data obtained, the factors influencing their amount were studied, and finally, general conclusions and suggestions were made.